Boomerang College Kids: Unemployment, Job Mismatch and Coresidence - Stefania Albanesi; Rania Gihleb; Ning Zhang (Institute of Labor Economics (IZA), 2022)
Labor market outcomes for young college graduates have deteriorated substantially in the last twenty five years, and more of them are residing with their parents. The unemployment rate at 23-27 years old for the 1996 college graduation cohort was 9%, whereas it rose to 12% for the 2013 graduation cohort. While only 25% of the 1996 cohort lived with their parents, 31% for the 2013 cohort chose this option. Our hypothesis is that the declining availability of 'matched jobs' that require a college degree is a key factor behind these developments. Using a structurally estimated model of child-parent decisions, in which coresidence improves college graduates' quality of job matches, we find that lower matched job arrival rates explain two thirds of the rise in unemployment and coresidence between the 2013 and 1996 graduation cohorts. Rising wage dispersion is also important for the increase in unemployment, while declining parental income, rising student loan balances and higher rental costs only play a marginal role.
Keywords: E24; J24; J12; E21; 330; coresidence; job mismatch; unemployment; student loans